The Impact of Digital Tools on Student Engagement in Secondary Schools of Sri Lanka: Dampak Alat Digital terhadap Keterlibatan Siswa di Sekolah Menengah di Sri Lanka - Dileepa Thathsara Olokku Patabendige (Yayasan Nurul Musthafa, 2026)
In Sri Lanka, the use of digital learning tools in secondary schools has been increasing, but their impact on student engagement is not fully understood. This study aimed to examine how digital learning tools affect cognitive, emotional, and behavioural engagement of students. A mixed-methods design was used, combining quantitative and qualitative data. A total of 120 students from Grades 9 to 11 were selected using simple random sampling, and 10 teachers were selected purposively for interviews. Quantitative data were collected through a structured student engagement questionnaire and analysed using SPSS. Descriptive statistics and paired sample t-tests were applied to compare engagement levels before and after using digital tools. The results showed a significant increase in overall student engagement (p < 0.05), with improvements in attention, interest, participation, and motivation during digitally supported lessons. Qualitative data from teacher interviews and classroom observations supported these findings, highlighting that digital tools made lessons more interactive and engaging. Challenges such as limited access to devices and lack of teacher training were also reported. The study concludes that digital learning tools can positively enhance student engagement in Sri Lankan secondary schools if teachers are trained and schools provide proper infrastructure. The findings suggest the need for policies and support systems to make digital learning effective and inclusive. [Di Sri Lanka, penggunaan alat pembelajaran digital di sekolah menengah terus meningkat, namun dampaknya terhadap keterlibatan siswa belum sepenuhnya dipahami. Penelitian ini bertujuan untuk menguji bagaimana alat pembelajaran digital memengaruhi keterlibatan kognitif, emosional, dan perilaku siswa. Desain metode campuran (mixed-methods) digunakan dengan menggabungkan data kuantitatif dan kualitatif. Sebanyak 120 siswa dari Kelas 9 hingga 11 dipilih menggunakan pengambilan sampel acak sederhana, dan 10 guru dipilih secara purposif untuk diwawancarai. Data kuantitatif dikumpulkan melalui kuesioner keterlibatan siswa yang terstruktur dan dianalisis menggunakan SPSS. Statistik deskriptif dan uji-t sampel berpasangan diterapkan untuk membandingkan tingkat keterlibatan sebelum dan sesudah menggunakan alat digital. Hasil penelitian menunjukkan peningkatan yang signifikan dalam keterlibatan siswa secara keseluruhan (p < 0,05), dengan peningkatan pada aspek perhatian, minat, partisipasi, dan motivasi selama pelajaran yang didukung secara digital. Data kualitatif dari wawancara guru dan observasi kelas mendukung temuan ini, menyoroti bahwa alat digital membuat pelajaran menjadi lebih interaktif dan menarik. Tantangan seperti akses terbatas ke perangkat dan kurangnya pelatihan guru juga dilaporkan. Studi ini menyimpulkan bahwa alat pembelajaran digital dapat meningkatkan keterlibatan siswa secara positif di sekolah menengah Sri Lanka jika guru dilatih dan sekolah menyediakan infrastruktur yang memadai. Temuan ini menyarankan perlunya kebijakan dan sistem pendukung untuk membuat pembelajaran digital menjadi efektif dan inklusif.]